Development of a real-time biofeedback tool for martial arts coaching practice - Shan, G.; Evans, J.; Chang, S.-T. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Power and neural response are two vital elements in martial arts striking. Currently, there are no practical methods exist to present these aspects to practitioners in a training environment. Our study has developed one. Our method consisted of an optical signal system, EMG and 3D motion capture. The feedback provided was generated by a selfdeveloped dynamic calculation programs using kinematics and EMG data as input. The results showed that our system provided both total power and its components (i.e. linear & angular) of a striking as well as the related response time. Since the method offers feedback of power intensity, attack accuracy, central and peripheral reaction time to practitioners in a quasi-training environment, it has great potential to become a real-time biofeedback tool in practice for increasing training efficiency and effectiveness.